Plasma-assisted CO2 and N2 conversion to plant nutrient - Attri, Pankaj; Okumura, Takamasa; Takeuchi, Nozomi; Kamataki, Kunihiro; Koga, Kazunori; Shiratani, Masaharu (Frontiers in Physics, 2023)
Colossal research on CO2 and N2 conversion using non-thermal plasma (NTP) technology has been ongoing since many years. The primary focus is on CO and NH3 production through CO2 and N2 conversion, respectively, with high conversion efficiency and low energy consumption with or without catalysts. Although in the present study, we propose that the NTP can assist in converting CO2 and N2 to plant nutrients in the form of plasma-treated/activated water. We used a homemade streamer plasma device and produced plasma-activated water (PAW) using CO2 and N2 feed gas, CO2-activated water (CAW) and N2-activated water (NAW). Later, we used CAW and NAW to treat the radish seeds and evaluate the germination rate, germination percentage, and seeding growth. To understand the chemical changes in PAW after the NTP treatment, we performed a chemical analysis to detect NO2¯, NO3¯, NH4+, and H2O2 along with the PAW pH and temperature shift. Additionally, to understand the other species produced in the gas phase, we simulated chemical reactions using COMSOL Multiphysics® software. Our results show that NOx and NHx species are less produced in CAW than in NAW, but CO2-generated PAW offers a significantly more substantial effect on enhancing the germination rate and seeding growth than NAW. Therefore, we suggested that CO and H2O2 formed during CAW production trigger early germination and growth enhancement. Furthermore, the total plasma reactor energy consumption, NO3¯ and NH4+ selective production percentage, and N2 conversion percentage were calculated. To our best knowledge, this is the first study that uses plasma-assisted CO2 conversion as a nutrient for plant growth.